THE MODERN SOCRATIC METHOD: A STRATEGY TO ENHANCE INDONESIAN POLYTECHNIC STUDENTS’ ACTIVE LEARNING IN ENGLISH SPEAKING COURSE - Yohannes Telaumbanua; Yalmiadi Yalmiadi; Kotrini Kotrini (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
Lack of engagement, weak critical thinking skills, disfluency, limited vocabulary, timidity, and a preference for individual learning often lead to inactive participation in English-speaking classes. This study investigated the qualitative impacts of the Modern Socratic Method (MSM) on Indonesian Polytechnic students’ active learning in an English-speaking course. Data were collected through complete participant observation and unstructured interviews, and analyzed using the Miles and Huberman interactive model. Credibility and transferability procedures ensured trustworthiness. The study was conducted over two semesters at Padang State Polytechnic with 54 students from two classes. Before the intervention, Class A and Class B obtained mean speaking performance scores of 50 and 60, respectively, both categorized as low. After the MSM was implemented, the means increased substantially to 85 (Class A) and 88 (Class B). The improvement was linked to MSM’s emphasis on continuous questioning, interactive discussion, logical argumentation, risk-taking in expressing opinions, and peer collaboration. These activities enhanced students’ fluency, expanded their vocabulary, strengthened critical thinking, built self-confidence, and fostered collaborative learning. The findings suggest that MSM can reduce reliance on lecture-based instruction in polytechnic English classes and improve students’ self-efficacy in managing speaking anxiety. This method holds promise for broader application in higher education contexts where active participation is essential.